Progress in immune microenvironment, immunotherapy and prognostic biomarkers in pediatric osteosarcoma - Zhang, Lin; Jiang, Haoming; Ma, Haichao (Frontiers in Immunology, 2025)
Pediatric osteosarcoma, the most prevalent primary malignant bone tumor in children, is marked by aggressive progression and a generally poor prognosis. Despite advances in treatment, including multi-agent chemotherapy, survival rates remain suboptimal, with metastasis, particularly to the lungs, contributing significantly to mortality. The tumor microenvironment plays a crucial role in osteosarcoma progression, with immune cells such as tumor-associated macrophages and T lymphocytes significantly influencing tumor behavior. The immunosuppressive environment, dominated by M2 macrophages, contributes to immune evasion and poor therapeutic outcomes, though recent findings suggest the potential for reprogramming these cells to enhance immune responses. This review provides a comprehensive overview of the immune landscape in pediatric osteosarcoma, with a focus on the role of immune cells and their interactions within the tumor microenvironment (TME). It examines the impact of immune checkpoints, genetic mutations, and inflammatory pathways on osteosarcoma progression, highlighting their contribution to tumor immune evasion and disease advancement. Additionally, emerging immunotherapeutic strategies, such as immune checkpoint inhibitors, macrophage reprogramming, and antibody-based therapies, are summarized in detail, showcasing their potential to improve therapeutic outcomes.